Studying cerebellar circuits by remote control of selected neuronal types with GABA-A receptors - Wisden, William; Murray, Andrew J.; McClure, Christina J.; Wulff, Peer (Frontiers in Molecular Neuroscience, 2009)
Although GABA-A receptor-mediated inhibition of cerebellar Purkinje cells by molecular layer interneurons (MLIs) has been studied intensely on the cellular level, it has remained unclear how this inhibition regulates cerebellum-dependent behaviour. We have implemented two complementary approaches to investigate the function of the MLI-Purkinje cell synapse on the behavioral level. In the first approach we permanently disrupted inhibitory fast synaptic transmission at the synapse by genetically removing the postsynaptic GABA-A receptors from Purkinje cells (PC-Δγ2 mice). We found that chronic disruption of the MLI-Purkinje cell synapse strongly impaired cerebellar learning of the vestibular occular reflex (VOR), presumably by disrupting the temporal patterns of Purkinje cell activity. However, in PC-Δγ2 mice the baseline VOR reflex was only mildly affected; indeed PC-Δγ2 mice showed no ataxia or gait abnormalities suggesting that MLI control of Purkinje cell activity is either not involved in ongoing motor tasks or that the system has found a way to compensate for its loss. To investigate the latter possibility we have developed an alternative genetic technique; we made the MLI-Purkinje cell synapse selectively sensitive to rapid manipulation with the GABAA receptor modulator zolpidem (PC-γ2-swap mice). Minutes after intraperitoneal zolpidem injection, these PC-γ2-swap mice developed severe motor abnormalities, revealing a substantial contribution of the MLI-Purkinje cell synapse to real time motor control. The cell-type selective permanent knockout of synaptic GABAergic input, and the fast reversible modulation of GABAergic input at the same synapse illustrate how pursuing both strategies gives a fuller view.